Influence of elbow orientation on solid particle erosion for multiphase flow - Khan, R. (Springer Science and Business Media Deutschland GmbH, 2020)
Erosive wear of equipment in hydrocarbon and mineral processing pipelines can occur under multiphase flow. The 90Â° elbow configuration is a common flow changing device in the pipeline network used to redirect the flow direction. This paper highlights a CFD approach to study erosion-induced damage in 90Â° elbows due to the transportation of sand particles in the carrier phase. A discrete phase modeling (DPM) technique is employed to decouple the relationship of elbow orientation and erosion-induced damage in 90Â° elbows. The computational geometry and simulation parameters consist of horizontal to horizontal (HâH), horizontal to vertical (HâV), and vertical to horizontal (VâH) orientated 90Â° elbows with 50.8Â mm inner diameter and fine sand of 50Â Î¼m size entertains in a liquid phase at 5Â m/s flow velocity. The high erosion zones have been located near the outlet of the 90Â° elbow under fine particle impact with a maximum erosion rate of 5.5Â mm/year in horizontalâvertical (HâV) oriented elbow. Â© Springer Nature Singapore Pte Ltd 2020.